Acute Pancreatitis and Recurrent Acute Pancreatitis in Children: A 10-Year Retrospective Study - Chaohui Wang; Bao Fu; De Su; Ping Huang; Xiaoyun Fu (Gastroenterology Research and Practice)
Aim. To compare the clinical characteristics of acute pancreatitis (AP) and recurrent acute pancreatitis (ARP) in children. Method. From January 2011 to January 2021, a total of 275 pediatric patients with AP admitted to a tertiary teaching hospital were enrolled. Results. The median age of 275 children was 12.0 years. Among them, 55 cases were ARP. The leading causes of pediatric pancreatitis were biliary tract and virus infection. The percent of male in the AP group was higher than that in the ARP group. Viral infection in the AP group were higher than that in the ARP group, but anatomical abnormalities were lower than those in the ARP group. The incidence of pancreatic pseudocysts in the ARP group was higher than that in the AP group. The median interval time from AP to ARP was 3.0 months. Conclusion. The main causes of pediatric pancreatitis were biliary tract and virus infection in the study. AP caused by virus infection seems to be less likely to develop into ARP. Female and anatomical abnormality are risks of ARP. Children with ARP are more likely to be complicated with pancreatic pseudocyst. There was no difference in ICU admission or mortality between AP and ARP.